MOTIVASI PETANI DALAM PENGELOLAAN USAHATANI PADI BERBASIS KEARIFAN PADA DAERAH ALIRAN SUNGAI (DAS) DI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Kurima, Yiyana; Sayamar, Eri; Kausar, Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purposes of this study are : 1) wisdom is still no longer be maintained by farmers in rice farming in Kuantan Tengah District of Kuantan Singingi Regency, and why it was and is not maintained anymore. 2) Knowing how importance and strength of wisdom of rice farming in Kuantan Tengah District of Kuantan Singingi Regency 3) Knowing how the motivation of farmers in rice farming wisdom based on river basin areas. The survey method was used in the research by population of respondents were 313 samples from Sawah Taluk and Pulau Aro village. The sampling technique was using Snowball Sampling. In terms of analyzing the data are Descriptif, Diagram Kartesius, and Scale of Liker's Summated Rating. The Result showed that number of wisdom in Sawah Taluk and Pulau Aro Village is totaled 38 wisdom that still exists and is not retained, as many as 22 wisdom that used to exist and as many as 16 wisdom is not maintained. Importance and strength of wisdom there are 22 that are considered to have the and interests of rice farmers in the watershed (DAS) is still there. Based on the results of the Likert's motivation Internal Farmers Against Wisdom got an average rating of 3.02, which means quite good, while based on the results of the Likert's external motivation Farmers Against Wisdom got an average rating of 2.98, which means quite good. Keywords: Motivation, Farmer,Wisdom